Clinical features and prognosis of patients with anti-GBM disease combined with mesangial IgA deposition - Ning, Wei; Zhao, Ya-fei; Liu, Ya-ru; Qi, Yuan-yuan; Zhao, Zhan-zheng (Frontiers in Immunology, 2024)
Anti-GBM diseases combined with IgA deposition in the mesangial region are rarely described.We compared the clinical, pathologic features, and renal prognosis of patients with anti-GBM disease combined with mesangial IgA deposition versus those with classical anti-GBM disease.There were 25 patients with anti-GBM disease combined with mesangial IgA deposition confirmed by renal pathological biopsy, accounting for 34.72% of all patients. Among them, 23 patients were included in the study, 17 of whom were female, accounting for 73.91%. Their median age was 44 years, and their age distribution was unimodal. The proportion of oliguria or anuria in patients with anti-GBM disease combined with mesangial IgA deposition was significantly lower than that in patients with classic anti-GBM disease (13.04 vs.42.31%, p=0.030). Their 24-hour urinary protein excretion was significantly higher[median:3.25vs.1.12g/24h, Interquartile range(IQR):1.032 3.945vs.0.63 1.79g/24h, p=0.020], serum creatinine(SCr) level at the initial diagnosis was lower(median:456.0vs.825.5μmol/L, IQR:270.0 702.0vs.515.8 1231.2μmol/L, p=0.002), peak SCr level was lower (median: 601.0vs.907.2μmol/L, IQR: 376.5 937.0vs.607.0 1361.2μmol/L, p=0.007), and their serum complement 3(C3) level was higher(median: 1.275vs.1.015g/L, IQR:1.097 1.462vs.0.850 1.220g/L, p=0.027). They had better renal outcomes during followup(p<0.001). After adjustment for hypertension, oliguria or anuria, and crescents%, IgA deposition in the mesangial region was still an independent protective factor(p=0.003) for ESRD in anti-GBM patients. Hypertension(p=0.026) and SCr levels at initial diagnosis(p=0.004) were risk factors for renal prognosis in patients with anti-GBM disease combined with mesangial IgA deposition. Patients with anti-GBM disease combined with mesangial IgA deposition have less severe renal impairment and better renal prognosis than patients with classic anti-GBM disease.